DEVELOPMENT OF INNOVATION INFRASTRUCTURE IN COUNTRIES WORLDWIDE - Oleksenko, Liliia (Public Management and Policy, 2024)
The article examines current trends in the development of innovation infrastructure in different countries of the world. Innovation infrastructure plays a key role in stimulating economic growth and ensuring the competitiveness of national economies. The purpose of the study is to analyse the functioning of innovation infrastructure, its main elements and models, and to identify best practices that can be adapted for development in Ukraine. The article conducts a thorough analysis of the definitions of the concept of innovation infrastructure and its tasks, including ensuring interaction between science, education and production, information support, financing of innovation projects and staffing. The key elements of the innovation infrastructure, such as science and technology parks, technopolises, business incubators and spin-off firms, which contribute to the intensification of innovation activity, are considered. The features of the American, European, Japanese and Chinese models of technology parks are studied. It has been found that the American model is the most advanced and is widely used as a basis for the creation of technology parks in the world. European technology parks are focused on small and medium-sized businesses, while the Japanese model involves the construction of new cities to integrate research centres and industrial production. The Chinese model is based on the active attraction of foreign investment and government support. The development of innovation infrastructure is critical to enhancing the innovation potential of the economy. Ukraine can use the experience of leading countries to create an effective innovation system that will contribute to economic growth, productivity and integration into global markets. Implementation of the proposed areas of infrastructure development, such as the introduction of technology parks and business incubators, will help create a favourable environment for innovation.